PENGARUH PANDEMI COVID-19 TERHADAP PRODUKTIVITAS, ETOS KERJA DAN MOTIVASI KARYAWAN SELAMA BEKERJA DI RUMAH (WFH) - Nuniek Dewi Pramanik (POLITEKNIK PIKSI GANESHA, 2021)
This study aims to know the impact of the Corona or Covid-19 Virus on work ethic, productivity and employee motivation. Besides, it is motivated by the Covid-19 Virus which is indirectly changes the work patterns of employees or labor both in the scope of government, agencies, the private sector, and others. One effect is working at home or WFH. Thus, the readers can understand how the Covid-19 Virus pandemic affects employee or workforce performance. This study has implications for businesses that want to know the measurement of the work from home (WFH) policies effectiveness. This study used descriptive qualitative and conducted literature studies either through journals, books, websites, and several other literary media. The results showed that the Covid-19 Virus pandemic had an influence on work productivity, work ethic, and motivation of employees or labor. On the other hand, the influence is based on several factors based on the employee attitudes during or when working. Keywords: The Effect of Covid-19, Work from Home (WFH), Motivation, Productivity, and Work Ethic.